An investigation on residual stress and fatigue life assessment of T-shape welded joints. (November 2022) - Samadi, Farzaneh; Mourya, Jeetendra; Wheatley, Greg; Nizam Khan, Mohammed; Masoudi Nejad, Reza; Branco, Ricardo; Macek, Wojciech
Highlights: This paper aims to evaluate the residual stress and fatigue life of T -type welded joints. The fatigue tests were conducted under uniaxial loading. The compressive residual stress increases with an increase in weld pass. The triple-pass welded joint obtained enhanced fatigue strength with optimum compressive residual stress. Multi-pass welding in different directions influences the change of residual stress and fatigue life. Abstract: This paper aims to quantitatively evaluate the residual stress and fatigue life of T-type welded joints with a multi-pass weld in different direction. The main research objectives of the experimental test were to test the residual stress by changing direction along with multiple wielding passes and determine the fatigue life of the welded joints. The result shows that compressive residual stress increases in the sample gradually from single-pass weld to double and triple-pass weld. Moreover, the fatigue life of the specimen also gradually improves with an increasing number of welding passes. Performing multi-pass welding in different directions affects the material's residual stress and fatigue life, which is an essential factor to consider for assuring the strength of the welded joint.